Uncertainty quantification for the CO2 storage efficiency in heterogeneous saline aquifers: The impact of variability in the lithology distribution - Afanasyev, Andrey; Sypchenko, Irina; Andreeva, Anna; Grechko, Sergey; Dymochkina, Maria; Pavlov, Vladimir; Maksakov, Kirill; Tsvetkova, Yulia; Vedeneeva, Elena; Chernova, Anna; Penigin, Artem (International journal of greenhouse gas control, 2025)
Geological storage of anthropogenic CO2 can require a preliminary evaluation and ranking of subsurface reservoirs characterized by limited geophysical data. On the basis of regional concepts and trends, only some geostatistical variables can be estimated for the potential storage reservoirs near a CO2 emitter. Consequently, the storage efficiency may be subject to a substantial uncertainty caused by the variability in the heterogeneous distribution of geological parameters, which details are not exactly known without extensive geophysical surveys. We evaluate that uncertainty by the numerical modeling of the CO2 storage efficiency in open heterogeneous aquifers. Using geostatistical modeling, we generate a large dataset of synthetic heterogeneous reservoir models characterized by various lithofacies ratios and distributions. We then simulate the injection of CO2 through a standalone vertical well to propagate the uncertainty forward to the storage efficiency. We show that the efficiency is characterized by a significant variance. Through an extensive parametric study of the statistical characteristics, we propose several recommendations for the CO2 storage site selection in the regional surveys. We show that the storage is more efficient in aquifers built of thin and extended reservoir interlayers at a specific net-to-gross ratio. The heterogeneity should also be isotropic in the lateral directions. We propose useful scaling relationships for the efficiency against the variogram ranges and the net-to-gross ratio. Finally, we show that the uncertainty in the efficiency cannot significantly be reduced using the well logging data. [Display omitted] •CO2 storage efficiency in heterogeneous aquifers is characterized by large variance.•Efficiency is evaluated against the lithofacies proportions and distribution.•Geological storage of CO2 is more efficient in layered reservoirs.•CO2 storage is more efficient in aquifers with a specific net-to-gross ratio.•Well logging at a standalone well cannot reduce the uncertainty in efficiency.